Предмет: Алгебра,
автор: ИринF121314
решите уравнение
(х-1)(х-4)(х+7)=х(х+1)²
Ответы
Автор ответа:
0
(х-1)(х-4)(х+7)=х(х+1)²
(х²-х-4х+4)(х+7)=х(х²+2х+1)
(х²-5х+4)(х+7)=х³+2х²+х
х³-5х²+4х+7х²-35х+28=х³+2х²+х
х³-5х²+4х+7х²-35х+28-х³-2х²-х=0
-32х=-28
х=-28:(-32)
х=7/8
(х²-х-4х+4)(х+7)=х(х²+2х+1)
(х²-5х+4)(х+7)=х³+2х²+х
х³-5х²+4х+7х²-35х+28=х³+2х²+х
х³-5х²+4х+7х²-35х+28-х³-2х²-х=0
-32х=-28
х=-28:(-32)
х=7/8
Автор ответа:
0
раскрываем скобки, получаем: (x^2-5x+4)(x+7)=x(x+1)^2; x^3-5x^2+4x+7x^2-35x+28=x^3+2x^2+x; x^3-x^3+2x^2-2x^2-31x-x=-28; -32x=-28; x=28/32; x=7/8; x=0,875
Похожие вопросы
Предмет: Математика,
автор: elena01yan78
Предмет: Математика,
автор: ruppel551202
Предмет: Русский язык,
автор: Аноним
Предмет: Химия,
автор: КШС